Effect of drill geometry and drilling parameters on the formation of adhesion layer in drilling composite-metal stack- up material / M H Hassan ...[et al.] - Hassan, M H; Abdullah, J; Mahmud, A S; Supran, A (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
Drilling of two very contrasting materials, composite-metal stack-up in one shot is a necessary and critical process in aircraft structure manufacturing. This drilling process is very complicated because it involves many parameters, and therefore requires systematic study. However no related publication is yet found on this subject. This paper presents a fundamental approach to determine the best combination of geometry and drilling parameters for drilling a stack-up Carbon Fibre Reinforced Plastic and aluminium 7075- T6 materials which lead to longer tool life. The approach is based on a combination of Fractional Factorials (2k-3) techniques where the main effect for each parameter was also identified. The experimental array comprises of four geometry parameters and two drilling parameters, performed in a single shot drilling process. The wear formation at the margin and cutting lips location were observed using scanning electron microscope. In order to quantify the adhesion wear that formed after the drilling process, the percentage of adhesion layer (PAL) was determined and the main effect for each geometry and drilling parameters of twist drill was further analysed. The ideal combination between the tool geometry and drilling parameters that produced a minimum PAL was identified.